Threshold crytography in organizational based E-commerce : an E-cheque application - Wang, Bin (2008)
This thesis investigates feasibility of employing threshold signature scheme in place of the multiple signature arrangement within the FSTC’s framework in practice, while still accomplishing collective approvals over an opened network by mobile trustees carrying only hand held devices of limited capability.